2011
DOI: 10.1007/s00467-011-1781-5
|View full text |Cite
|
Sign up to set email alerts
|

Fetal programming of renal function

Abstract: Results from large epidemiological studies suggest a clear relation between low birth weight and adverse renal outcome evident as early as during childhood. Such adverse outcomes may include glomerular disease, hypertension, and renal failure and contribute to a phenomenon called fetal programming. Other factors potentially leading to an adverse renal outcome following fetal programming are maternal diabetes mellitus, smoking, salt overload, and use of glucocorticoids during pregnancy. However, clinical data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…There are several proposed mechanisms that may contribute to fetal renal underdevelopment [28]. Changes in the growth factors in the uterus can clearly play an important role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several proposed mechanisms that may contribute to fetal renal underdevelopment [28]. Changes in the growth factors in the uterus can clearly play an important role.…”
Section: Discussionmentioning
confidence: 99%
“…Proteinuria is a biomarker reflecting progressive renal dysfunction [52]. It has been suggested that reduced nephron number at birth can lead to the adaptation of glomerular hypertrophy and hyperfiltration in order to maintain sufficient renal function [26], [28], [39], [53]. Prolonged hyperfiltration can in turn lead to hyperfiltration injury in the long term, resulting in structural injury and functional deterioration in adulthood [26].…”
Section: Discussionmentioning
confidence: 99%
“…Because the estimated prevalence of obesity in women of reproductive age in the United States is 31.8%, and rates are similar in other developed countries, including the United Kingdom and Australia (19), maternal obesity may set forth the above-described pathophysiologic mechanisms from early in prenatal life (20). This concept that adverse conditions during early life increase the susceptibility to chronic diseases in adulthood underpins the theory of the developmental origins of health and disease (21). Fetal programming has been implicated in the development of conditions such as cardiovascular disease, hypertension, T2D, obesity, and CKD (22).…”
Section: Fetal Programming Maternal Transmission Of Disease and Epimentioning
confidence: 99%
“…In addition, there is an almost tenfold variation in normal nephron numbers, ranging from a little over 200,000 to over 2.5 million nephrons per kidney [3]. Some of this variation may be explained by genetic differences, and many environmental factors may influence final nephron numbers as well [8]. …”
Section: Nephron Numbersmentioning
confidence: 99%